Warm beach, warmer turtles: Using drone-mounted thermal infrared sensors to monitor sea turtle nesting activity - Sellés-Ríos, Bárbara; Flatt, Eleanor; Ortiz-García, Johan; García-Colomé, Júlia; Latour, Orane; Whitworth, Andrew (Frontiers in Conservation Science, 2022)
For decades sea turtle projects around the world have monitored nesting females using labor-intensive human patrolling techniques. Here we describe the first empirical testing of a drone-mounted thermal infrared sensor for nocturnal sea turtle monitoring on the Osa peninsula in Costa Rica. Preliminary flights verified that the drone could detect similar sea turtle activities as identified by on-the-ground human patrollers – such as turtles, nests and tracks. Drone observers could even differentiate turtle species tracks, detect sea turtle hatchlings, other wildlife, and poachers. We experimented in the pilot flights to determine optimal parameters for detection by testing different thermal visualization modes, drone heights, and gimbal angles. Then, over seven nights, we set up a trial to compare the thermal drone and operators' detections with those observed by traditional patrollers. Our trials showed that thermal drones can record more information than traditional sea turtle monitoring methods. In x30 flights of 21-25 minutes, the drone and observer detected 20% more sea turtles or tracks than traditional ground-based patrolling, over x23 two-person patrols of 40-50 minutes (flights and patrols carried out across the same nights at the same time and beach). In addition, the drone operator detected 39 animals/predators and 3 poachers that patrollers failed to detect. Although the technology holds great promise in being able to enhance detection rates of nesting turtles and other beach activity, and in potentially keeping observers safer, we detail challenges and limiting factors in drone imagery, current cost barriers, and technological advances that need to be assessed and developed before standardized methodologies can be adopted. We suggest potential ways to overcome these challenges and recommend how further studies can help to optimize thermal drones to enhance sea turtle monitoring efforts worldwide.